Treating adult substance abuse using family behavior therapy : a step-by-step approach - Donohue, Brad.; Allen, Daniel N. (Hoboken, N.J. : John Wiley & Sons, 2011)
'Family Behavior Therapy (FBT) is an evidence-based treatment that helps adult patients address substance abuse as well as coexisting problem behaviors, including family dysfunction, employment, and mood disorders. Donohue and Allen are the premier researchers and practitioners of FBT, and their book is the first to provide the practical, step-by-step guidance needed to use this cost-effective intervention method with clients. It contains descriptions of each component of the treatment in addition to case examples, worksheets, and handouts. Counselors, therapists, and social workers will appreciate this'how-to' behavioral approach to therapy'--Provided by publisher.
Book is accompanied by one computer optical discs entitled' Treating adult substance abuse using family behavior therapy : a step-by-step approach' bearing the same call number and availaible at Bahagian Koleksi Media.
Includes bibliographical references and indexes.
System requirements: 120 MHz or faster processor; 32 MB of total RAM, 64 MB recommended; A CD-ROM drive.
Keywords: Substance abuse -- Treatment; Family psychotherapy; Behavior therapy